THE EFFECT OF LEAD ON DUST AND NON-SMOKING WORKERS IN SOME GAS STATIONS IN KIRKUK GOVERNORATE (Academia Science Repository, 2023)
This study was completed in the city of Kirkuk, where the study of environmental pollution with the element lead in a number of government gas stations in the province of Kirkuk, which has a lot of cars gathering to refuel, causing an increase in the proportions of pollutants coming out of car exhaust, including lead. This work studied five sites, namely: Andalusia gas station, Al-Mutwra gas station, Baba Karkar gas station and Uqba bin Nafi gas station. The fifth and final site is the control site in the Domiz area in the south of the province. The study sampled the ground of these stations (dust), and measuring the concentration of lead in them and measuring some chemical factors of the soil for a period of six months, a sample every month, starting from November 2022 until April 2023. Then, the blood samples from some workers in those stations for non-smokers were collected and the element lead in those samples was examined.